Ladder Diagram Design Based On Cascade Method For Selection And Assembling Part On Dual Conveyor Plant - Eka Iskandar; Mochammad Rameli; Rafly Adiyat (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Abstract— The transfer of goods from one place to another in the production process in a common industry we encounter using conveyors. Conveyors have replaced human labor used in moving production goods from one place to another in the industry. By using conveyors, the transfer time can be reduced and not dependent on humans anymore. Conveyor control can use a controller in the form of a PLC. PLC programming can use many methods, one of which is the cascade method. The beginning of the development of this method is widely used in pneumatic systems, but as time goes by this method is used in completing sequential systems. The ideal cascade method is used for sequential processes without an iterative process, the theory is easy to understand, the results are easy to implement. In this study the type of PLC used is CPM1 from OMRON. By using Cascade method, the result from construction of ladder diagram is obtained by 59 rung, 6 timer, 18 relay, and the program capacity is 3 KB.Keywords: Conveyor, PLC, Ladder diagram, Cascade method, relay group.